Case report: Drug reaction with eosinophilia and systemic symptoms (DRESS) induced by ceftazidime in a connective tissue disease (CTD) patient - Dai, Rui; Niu, Ziran; Yang, Yang; Liu, Xin; Zhang, Bo (Frontiers in Pharmacology, 2024)
Drug reaction with eosinophilia and systemic symptoms (DRESS) is a rare and severe cutaneous adverse drug reactions (SCARs) with high mortality. Antibiotics are the most frequent causative agents related to DRESS. However, it is rarely reported in cephalosporins, especially for ceftazidime. Here, we reported a case of ceftazidime-induced DRESS with HLA genotypic polymorphism as a risk factor. A 58-year-old woman with connective tissue disease was intravenously infused with ceftazidime for the treatment of pneumonia and intestinal infection, followed by the presence of fever, rash, and hematologic and hepatic laboratory abnormalities. DRESS was diagnosed and the positive polymorphism in HLA-B*15:02 was found. Our case illustrated the necessity to clarify the patho-mechanism and the use of pretreatment HLA analysis to prevent ceftazidime-related DRESS may be a valuable option soon.